About abortion: terminating pregnancy in twenty-first-century, de Carol Sanger - Peres Gediel, José Antônio (Revista de Direito Civil Contemporâneo, 2020)
Dados bibliográficos: SANGER, Carol. About abortion: terminating pregnancy in Twenty-First-Century America. Cambridge: The Belknap Press of Harvard University Press, 2017.